Penyuluhan Makanan dan Obat yang Aman untuk Anak di KB-TK Alam Insan Kamil - Tamzil Azizi Musdar; Wahyu Nuraini Hasmar; Ika Lismayani Ilyas (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The pattern of food and medicine consumption among children is a crucial thing that is important for parents and teachers to pay attention to at school. It is very important to provide guidance and reinforcement regarding hygiene, sanitation or food safety to food makers, including parents and the implementation team or school canteen organizers. Based on the results of initial observations, it was found that the food presentation met standards, but there were still teachers who did not understand how to use cooking utensils correctly. The aim of this service is to increase teachers' knowledge in terms of providing nutritious and safe food and the use of medicines that are commonly given in the school environment. The method used in this service is providing material in the form of counseling. The results of the service showed that there was an increase in the knowledge of service participants after being given counseling material in the form of providing food and medicine in a safe and hygienic manner.